2021
DOI: 10.1007/s00221-020-06008-1
|View full text |Cite
|
Sign up to set email alerts
|

Conscious awareness modulates processing speed in the redundant signal effect

Abstract: Evidence for the influence of unaware signals on behaviour has been reported in both patient groups and healthy observers using the Redundant Signal Effect (RSE). The RSE refers to faster manual reaction times to the onset of multiple simultaneously presented target than those to a single stimulus. These findings are robust and apply to unimodal and multi-modal sensory inputs. A number of studies on neurologically impaired cases have demonstrated that RSE can be found even in the absence of conscious experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…Interestingly, reaction times in the Visual + Audio condition did not differ from the Single Audio condition when participants reported being unaware of the visual stimulus. These findings are also consistent with the association between subjective awareness and reaction time under CFS with previous findings indicating that for unimodal visual RSE to occur, the participant need to report some level of awareness of masked targets [29]. More importantly, the incidence of aware trials was higher for the combined audio and visual stimuli than for the visual stimulus alone, again contributing to the evidence of the possibility that increased reported awareness is caused by multisensory integration.…”
Section: Summary Of Experimentssupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, reaction times in the Visual + Audio condition did not differ from the Single Audio condition when participants reported being unaware of the visual stimulus. These findings are also consistent with the association between subjective awareness and reaction time under CFS with previous findings indicating that for unimodal visual RSE to occur, the participant need to report some level of awareness of masked targets [29]. More importantly, the incidence of aware trials was higher for the combined audio and visual stimuli than for the visual stimulus alone, again contributing to the evidence of the possibility that increased reported awareness is caused by multisensory integration.…”
Section: Summary Of Experimentssupporting
confidence: 90%
“…We expected there to be faster responses in the Visual + Audio condition compared to the Single Audio. We expected the slowest performance in the Single Visual condition, as previous findings have shown that a single weak visual target presented under a CFS mask often goes unnoticed, and that if reaction time response is made to its detection it tends to be slow [29].…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The goal of the present study was to systematically investigate the effect of spatial attention on MSI through two experiments and determine whether and why there were opposite effects of exogenous and endogenous orienting on MSI. We replicated a well-known multisensory advantage (Cederblad et al, 2021; Hershenson, 1962; Lunn et al, 2019; Tang et al, 2016), i.e., faster responses to multisensory stimuli than to unisensory stimuli (Figures 2 and 5). Furthermore, as expected, we found that exogenous and endogenous orienting induced by the directionality and predictability of the cue modulated MSI differently.…”
Section: Discussionsupporting
confidence: 68%